Iron(ii) β-ketiminate complexes as mediators of controlled radical polymerisation. Issue 40 (9th May 2016) - Lake, Benjamin R. M.; Shaver, Michael P.
Abstract : A series of novel iron(ii ) β-ketiminate complexes have been prepared and screened in styrene and methyl methacrylate CRP. Abstract : A series of tridentate, ONO- and ONN-chelating β-ketiminate ligands were synthesised via condensation reactions, and complexed with iron(ii ) using [Fe(N(SiMe3 )2 )2 THF]. The complexation reactions proceeded in high yields to generate novel, monomeric, tetracoordinate iron(ii ) complexes, each bearing a bis(trimethylsilyl)amide ligand, as confirmed by X-ray crystallography. These complexes were amenable to further reaction (protonolysis) with alcohols and phenols, generating alkoxide/phenolate-containing complexes that were dimeric in the solid state. All complexes synthesised were screened as potential mediators of the controlled radical polymerisation (CRP) of styrene and methyl methacrylate under both atom transfer radical polymerisation (ATRP) and organometallic mediated radical polymerisation (OMRP) conditions. Whilst all of the complexes were relatively poor ATRP mediators under the conditions used here, regardless of monomer choice, dispersities ( Đ ) as low as 1.58 for styrene and 1.23 for methyl methacylate polymerisation under OMRP conditions could be achieved. The better performance in methacrylate polymerisation suggests the formation of a stronger metal–carbon bond in these systems. In particular, the use of a β-ketiminate ligand functionalised with an N, N -dimethylethylene pendant arm and a 2, 6-diphenylphenolate ligand affords a potential Fe-based mediator of methyl methacrylate OMRP.